The artists' and writers' cookbook : a collection of stories with recipes - Garrett, Natalie Eve; Porter, Amy Jean (powerHouse Books, 2016)
Inspired by a book from 1961, The (original) Artists' & Writers' Cookbook included recipes from the likes of Marcel Duchamp, Man Ray, Marianne Moore, and Harper Lee. This new, vibrantly illustrated version includes stories and recipes from Anthony Doerr, Leanne Shapton, Joyce Carol Oates, John Currin and Rachel Feinstein, Ed Ruscha, Neil Gaiman, Edwidge Danticat, Aimee Bender, Gregory Crewdson, James Franco, Francesca Lia Block, Swoon, Nelson DeMille, Rick Moody and Laurel Nakadate, Nikki Giovanni, T.C. Boyle, Lev Grossman, Roz Chast, Heidi Julavits, Marina Abramović, Curtis Sittenfeld, Julia Alvarez, and many others.